Hangar utility simulation as a traffic flow density scenario in Giwangan Market Yogyakarta - Marni Astuti; Yasrin Zabidi; Prasidananto Nur Santoso (Institut Teknologi Dirgantara Adisutjipto, 2020)
Giwangan Market as a fruit and vegetable wholesale market needs to be evaluated, organized and improved in the services. Currently, its development has undergone many changes. The hangar, which is the main block for loading and unloading fruits and vegetables, has shifted its function in several places. With the addition of semi-permanent buildings on the sides of hangars, the loading and unloading area are reduced and the entry and exit routes for vehicles are not functioning properly. 86% of vehicles with a tonnage of 2000 - 5000 kg that entered the Giwangan market were in the market for an average of 89.9 minutes. It is because the vehicle is not only loading and unloading but also selling in the market. So that other vehicles cannot load and unload. This study aims to measure the system performance which is estimated from the average actual travel time and the loading and unloading time of vehicles in the system. The alternative of rearranging hangar used is based on the development plan of the Giwangan Market Management Office. The simulation model has been verified and validated. The first rearrangement scenario is that all traders are moved to a new location (slaughterhouse). Second, the flow in and out of the hangar is one-way. Thus, the average vehicle in the system becomes 54.44 minutes and the hangar utility is 16.13% as an indicator that the hangar performance can be improved by increasing the number of vehicles capable of loading and unloading.